Temperature field measurements between a Bunsen flame and flat a cold plate by using PLIF. Issue 1 (1st April 2022) - Tolstoguzov, R V; Chikishev, L M
Abstract: The present experimental work reports on the temperature measurements in a Bunsen flame, covered by a flat cooled plate from the top. The temperature field is measured based on the planar laser-induced fluorescence method for hydroxyl radical (OH) during the excitation of excitation Q1 (8) line of the (1-0) band of the A 2 Σ + -X 2 Π electronic system. Thermometry was based on the imaging of the ratio of the fluorescence intensity for the band (2-0) and bands (0-0), (1-1). The paper presents the obtained temperature fields for the distances between the plate and the burner of 1, 2 and 3 calibres. The paper also concludes that the used method can be implemented using a single-pulse laser illumination and is effective for the detection of cold zones.